Peran Kepala Sekolah Dalam Meningkatkan Mutu Manajemen Sekolah di SDI Satu Atap Wara - Khomsaton Dwi Mansoben (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2023)
The purpose of the research was to determine the role of the principal as an educator in improving the quality of school management. To find out the role of the principal as an administrator in improving the quality of school management. To find out the role of the principal as a manager in improving the quality of school management. To find out the role of the principal as a supervisor in improving the quality of school management. The research method used is qualitative. By using this type of exploratory research. Sources of data used are primary data and secondary data. Data collection techniques used are observation, interviews, and documentation. The data analysis techniques used are; Reduction, Presentation and Conclusion. The results of data analysis in this study are related to the role of the principal in improving the quality of school management at SDI Satu Atap Wara, which will be explained further as follows: 1. The role of the principal as an educator in improving the quality of school management. 2. The role of the principal as an educator in improving the quality of school management. The Principal as Administrator in Improving the Quality of School Management. 3. The Role of the Principal as Manager in Improving the Quality of School Management. 4. The Role of the Principal as Supervisor in Improving the Quality of School Management.